Experiences of male irregular migrants during their migration process and reception in Spain: lessons learned from the COVID-19 pandemic - García-López, Dulcenombre de María; Jiménez-Lasserrotte, María del Mar; Briones-Vozmediano, Érica; Ruiz-Fernández, María Dolores; Hernández-Padilla, José Manuel; Granero-Molina, José (Frontiers in Public Health, 2024)
The causes behind migration movements are complex. The COVID-19 pandemic highlighted how several countries failed to respond to the virus adequately, while simultaneously infringing on people's rights. Male irregular migrants fled their countries of origin and embarked on a perilous migration journey to Spain. The highly restrictive COVID-19 measures and border closures affected the mobility of male irregular migrants, whose reception in the host country posed a challenge. It led to the establishment of emergency facilities to accommodate male irregular migrants affected by COVID-19, which had repercussions on their mental health. The aim of this study was to describe and understand the experiences of male irregular migrants throughout their migration process and reception in Spain during the COVID-19 pandemic. Methods: Qualitative descriptive study. Sixteen male irregular migrants participated in this study. Data were collected between January and March 2023 through 16 one-on-one in-depth interviews. Thematic analysis was used to analyse the qualitative data using ATLAS.ti computer software. Results: Three main themes emerged: (1) How the COVID-19 pandemic drove male irregular migrants to leave their countries of origin, (2) How COVID-19 lockdown policies affected the migration journey, and (3) Receiving male irregular migrants in a pandemic: a housing labyrinth marked by isolation and loneliness. Conclusion: The COVID-19 PAGE pandemic increased the social, employment and health inequalities experienced by male irregular migrants. Border closures exacerbated the migration journey and the social stigmatisation of this group, who were seen as carriers of the virus in both transit and host countries. Strict control measures in emergency and reception facilities had a significant psychological impact on the male irregular migrants due to the social isolation they experienced. Health institutions should develop programs to guarantee the care needs of irregular migrants.